2016
DOI: 10.1016/j.athoracsur.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Bolus of Erythropoietin on Renoprotection in Patients Undergoing Thoracic Aortic Surgery With Moderate Hypothermic Circulatory Arrest

Abstract: A single bolus administration of erythropoietin 500 IU·kg(-1) at anesthesia induction failed to provide renoprotection in patients who underwent thoracic aortic surgery with moderate hypothermic circulatory arrest. However, erythropoietin significantly reduced cardiac complications, and lowered the incidence of prolonged vasopressor dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…In 2 recent RCTs in which patients were randomized to a liberal (Hg <9.5 g/dL) or restrictive (Hg <7.5 g/dL) transfusion policy intraoperatively and postoperatively, there was no difference in postoperative outcomes including AKI . In addition, studies have failed to demonstrate any benefit in the use of erythropoietin in the prevention of postoperative AKI . Conventional ultrafiltration has been used to treat the hemodilutional effects of CPB circuits, but routine adoption does not seem to be efficacious, with a recent study demonstrating a higher adjusted risk of AKI …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2 recent RCTs in which patients were randomized to a liberal (Hg <9.5 g/dL) or restrictive (Hg <7.5 g/dL) transfusion policy intraoperatively and postoperatively, there was no difference in postoperative outcomes including AKI . In addition, studies have failed to demonstrate any benefit in the use of erythropoietin in the prevention of postoperative AKI . Conventional ultrafiltration has been used to treat the hemodilutional effects of CPB circuits, but routine adoption does not seem to be efficacious, with a recent study demonstrating a higher adjusted risk of AKI …”
Section: Resultsmentioning
confidence: 99%
“…Perioperative. Numerous pharmacological agents including levosimendan, [94][95][96][97] statins, 98-100 N-acetylcysteine, [101][102][103][104] sodium bicarbonate, [105][106][107][108] and erythropoietin [109][110][111][112][113] have, for the most part, failed to demonstrate benefit for the prevention of CS-AKI. A possible exception is dexmedetomidine, for which a number of small or low-quality studies found a reduction in the occurrence of AKI after cardiac surgery.…”
Section: Pharmacological Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should, however, be emphasized that in the largest study in ICU patients [215] AKI was only reported as an adverse effect and not clearly defined. Two more recent RCTs in the setting of thoracic aortic surgery [217] and contrast administration in diabetics [218] confirmed the absence of beneficial effect of EPO on the incidence of AKI or need for RRT in critically ill patients (ESM_2 Table S12).…”
Section: Hormonal Manipulationmentioning
confidence: 97%
“…The opposing results can possibly be attributed to lack of biopsied samples and the inherent variability in injury severity and outcome. Other human studies have conducted prophylactic administration of EPO and Pentoxifylline in patients undergoing cardiac surgery, a procedure with a high risk of inducing AKI [42][43][44][45][46]. In these studies, positive outcomes were associated with decreased inflammatory markers, including lower urinary NGAL, TNF α, IL-6, and C-reactive protein [42,46].…”
Section: Macrophage Polarization In Human Akimentioning
confidence: 99%